Promoting Health Tourism in India:An Exploratory Study on the Role of Specialty and Corporate Hospitals in Bangalore - Suresh, Satya (Indian Journal of Marketing, 2011)
Confederation of Indian Industries (CII) in association with Indian Healthcare Federation is working closely with the Government of India to evolve an enabling strategy to project India as a world-class health care destination. India has the potential to attract 1 million tourists per annum, which could contribute up to US $ 5 billion to the economy. India is witnessing 30 percent growth per annum in this sector. Nevertheless, the health tourism industry, which has immense potential in India, also faces a variety of challenges. The core drivers of this sector are the specialty hospitals, which should spear drive changes and sustain the momentum of health tourism in India. The role of the specialty hospitals and corporate run hospitals in promoting health tourism in India is the focus of this study. Hence, the objectives are: 1. To explore if corporate and specialty hospitals in Bangalore, help to promote health tourism to India. 2. To study if the corporate and specialty hospitals in Bangalore are addressing to the various issues that needs for the growth of health tourism in India. This study explores health care decision maker's views on how their hospital management contributes to the flow of medical tourism in India. Six in-depth interviews were conducted with an interview schedule involving the administrative head of super specialty hospitals in Bangalore. Interviewees described that the hospitals are putting efforts towards promoting medical tourism, but it has to be taken up more comprehensively as there are variety of issues outside the gamut of treatment and hospitalization-like fast track visa clearance for emergency cases. Coming together of the various services providers and strong lobbying would make the Government clear certain bottlenecks the industry is currently facing.